Phytogeographic of Bromelia L. (Bromeliaceae) in the State Paraiba Brazil - Moura, Debora Coelho; Souza, Maira Suenia Cavalcante de; Pereira, Thais Mara Souza; Marques, Ailson de Lima; Pontes, Ricardo Ambrosio de Soares de; Lucena, Maria de Fatima Araujo; Costa, Cassio Ricardo Goncalves da (Journal of Forests, 2021)
The Bromelia (Bromeliaceae) is part of the Poales taxonomic group, distributed in the Neotropical Ecosystems of South America, from sea level to altitudes of 5,000 meters in the Andes. In the Brazilian territory there were two settlements, one directly from the plateau of the Guianas and another across the Andes. The family stands out as one of the main taxa of the Brazilian flora, sheltering about 40% of the species of this family, in which 46 genera are recorded, of these 20 are endemic. In the state of Paraíba, because it has three distinct climatic regions, it originates a different phytogeographic distribution of this Family, so this study aims to perform a phytogeographic analysis of Bromelia L. (Bromeliaceae), to understand the distribution of the genus, registered in the state of Paraíba, eastern portion of the Northeast. Understand the gender distribution, registered in the state of Paraíba, eastern portion of the Northeast. In this study, two species, Bromelia karatas L. and Bromelia laciniosa Mart, were identified for the genus B. Karatas L. was found in the wetlands of Agreste and Litoral and also in the region of Sertão Paraíba state, in specific areas. Whereas, B. laciniosa, only in the regions of the Cariris Velhos, tectonic valley of the Curimataú and Seridó, that are inserted in the field of the Caatinga, but with influence of edaphoclimatic variabilities.